2021
DOI: 10.1002/ajoc.202100264
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐Phase Synthesis of Peptidomimetics with Peptide Backbone Modifications

Abstract: Peptidomimetics are a class of compounds with promising pharmacological properties. Peptidomimetics reduce limitations of peptides including low bioavailability, poor stability, and poor cell‐permeability. Peptide backbone modifications are a frequently used manipulation to reach desirable properties of the peptide molecules. The development of accessible synthetic methodologies plays an important role in peptidomimetic progress. Synthesis of peptidomimetics proceeds via solution and solid‐phase synthesis stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 144 publications
0
17
0
Order By: Relevance
“…Standard SPPS protocols have also been modified in order to adapt to the generation of peptidomimetic scaffolds. Accordingly, they were combined with click chemistry protocols, metal‐mediated reactions, N ‐alkylations, and N ‐acylations in order to incorporate diverse building blocks and functionalities [152] . As for traditional SPPS, one of the future development directions for the peptidomimetic solid‐phase synthesis will be the incorporation of green solvents and recyclable solid supports.…”
Section: Discussionmentioning
confidence: 99%
“…Standard SPPS protocols have also been modified in order to adapt to the generation of peptidomimetic scaffolds. Accordingly, they were combined with click chemistry protocols, metal‐mediated reactions, N ‐alkylations, and N ‐acylations in order to incorporate diverse building blocks and functionalities [152] . As for traditional SPPS, one of the future development directions for the peptidomimetic solid‐phase synthesis will be the incorporation of green solvents and recyclable solid supports.…”
Section: Discussionmentioning
confidence: 99%
“…The development of newer synthetic strategies to obtain peptidomimetic drugs besides the evolution of solid-phase peptide synthesis (SPPS), , essential for mimetics with strong peptide character, has led to growing interest in this class of therapeutics, as evidenced by the list of drugs approved by the Food and Drug Administration (FDA) in the past few years ().…”
Section: Peptidomimetics Launched In the Market And Under Clinical Tr...mentioning
confidence: 99%
“…The development of newer synthetic strategies to obtain peptidomimetic drugs besides the evolution of solid-phase peptide synthesis (SPPS), 42,43 Recently, El-Faham et al 44 reported that 21 drugs of peptide and peptidomimetic nature were approved by FDA between January 2015 and May 2021 and represent 5% of all drugs launched into the market. Most of these new drugs exhibited a high degree of peptide character and do not really show a small molecule peptidomimetic nature, probably suggesting that peptides are more successful in drug development than peptidomimetics.…”
Section: Peptidomimetics Launched In the Market And Under Clinical Tr...mentioning
confidence: 99%
“…The extraction of natural peptides can be expensive, but this problem is often overcome through solid phase peptide synthesis (SPPS) of the same or model peptides [ 72 ]. Sometimes, cytotoxicity, especially due to haemolytic activity, has been reported [ 28 , 73 ].…”
Section: Weak Points Of Ampsmentioning
confidence: 99%